“EQUINOXES” BY TIBERIU OLAH - Răzvan METEA (Studia Universitatis Babeş-Bolyai. Musica)
"Overwhelming dramatic tensions, lyricism going up to the the inner tear, fine humor with a touch of malice, overflowing colourful imagination, all embedded in a whole managed with unrivalled sense of time: a music you cannot pass by, which turns you upside down and brings you closer to the deep meanings of existence" (Olguţa Lupu)[1]. Not unlike grand personalities, Tiberiu Olah understood music on large areas and ample dimensions of time. He thoroughly researched and applied very well the expressive means of popular and classical instruments, as well as those of the human voice, but he especially explored Romanian folk dances and mainly their rhythm, suggestively expressed by the hidden language of modern percussion. The composer creates a world of celestial sonorities where musical time and space are very well outlined.